2021
DOI: 10.1093/ibd/izaa337
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease and Risk of Major Bleeding During Anticoagulation for Venous Thromboembolism

Abstract: Background Little is known about the bleeding risk in patients with inflammatory bowel disease (IBD) and venous thromboembolism (VTE) treated with anticoagulation. Our aim was to elucidate the rate of major bleeding (MB) events in a well-defined cohort of patients with IBD during anticoagulation after VTE. Methods This study is a retrospective follow-up analysis of a multicenter cohort study investigating the incidence and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…A retrospective study on 107 patients with IBD reported a higher event rate of major bleeding during anticoagulation, that is, 2.6 per 100 patient-years, but it still concluded that this risk was probably outweighed by the high risk of recurrent VTE. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study on 107 patients with IBD reported a higher event rate of major bleeding during anticoagulation, that is, 2.6 per 100 patient-years, but it still concluded that this risk was probably outweighed by the high risk of recurrent VTE. 24 …”
Section: Discussionmentioning
confidence: 99%
“…2.6 per 100 patient-years, but it still concluded that this risk was probably outweighed by the high risk of recurrent VTE. 24 Our study has several limitations, first that it is a retrospective chart review and the patients that were referred to our service for investigation and advice were most likely selected. Second, the number of patients, particularly those with IBD, is small.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Both IBD and AF are independently associated with a high risk of thromboembolic events. 9 Hence, the risk of ischemic events is further increased in patients with IBD who develop AF. The challenge is the increased risk of bleeding in patients with IBD on anticoagulation.…”
mentioning
confidence: 99%
“…The challenge is the increased risk of bleeding in patients with IBD on anticoagulation. 9 Considering that in IBD and AF patients on anticoagulation the risk of bleeding is outweighed by the risk of recurrent thromboembolism and that bleeding may be major but rarely fatal, the use of anticoagulation should be the treatment of choice. 9 Atherosclerosis and IBD are interrelated through common pathogenetic mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation